Perbandingan Hasil Belajar Model Pembelajaran Inquiry dengan Model Kooperatif Learning Tipe Number Head Together (NHT) dalam Mata Pelajaran (IPA) Kelas V SD Negeri 58 Kota Bengkulu - Asiyah Asiyah; Ahmad Walid; Adrian Topano (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
This study aimed to determine whether the science learning outcomes of grade V students who are taught using the NHT Model in SD Negeri 58 Bengkulu City. This study used two groups, namely class 5A with 31 people as the experimental group and class 5B with 31 people as the control group. The research variable consisted of independent variables, namely the Inquiry learning model and the NHT model, while the dependent variable was the science learning outcome. Based on the results of the study, it was found that the posttest results of class 5A students who used the Inquiry Learning Model, namely in the medium and high categories of 93% got a score of 60 to 100 while the learning outcomes of class 5B using the NHT Model were 81% getting a score of 50 to 90. shows that the science learning outcomes of grade V students who are taught using the Inquiry Learning Model are better than those using the NHT model in SD Negeri 58 Bengkulu City.